1996
DOI: 10.1159/000227621
|View full text |Cite
|
Sign up to set email alerts
|

Review of Tests for Monitoring Doxorubicin-lnduced Cardiomyopathy

Abstract: The objective of this review is to make physicians aware of new radionuclide methods to detect cardiac effects of chemotherapeutic drugs. This knowledge is important because of the limitations of the physical examination and the electrocardiogram for detecting early reversible cardiac damage. Presently left ventricular ejection fraction (LVEF) is routinely used to screen for cardiotoxicity. Since LVEF obtained by radionuclide angiocardiography is more accurate than the LVEF estimated by echocardiography, seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
0
11

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 28 publications
3
96
0
11
Order By: Relevance
“…The cycle was repeated every 3 weeks to a total of 10 cycles. Doxorubicin was discontinued if left ventricular ejection fraction (LVEF) decreased below 45% (Druck et al, 1984;Ganz et al, 1996). No radiotherapy was given during the study period.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The cycle was repeated every 3 weeks to a total of 10 cycles. Doxorubicin was discontinued if left ventricular ejection fraction (LVEF) decreased below 45% (Druck et al, 1984;Ganz et al, 1996). No radiotherapy was given during the study period.…”
Section: Chemotherapymentioning
confidence: 99%
“…Only endomyocardial biopsy has been considered to be sensitive and specific enough in predicting the development of CHF (Mason et al, 1978;Billingham and Bristow, 1984), but the invasiveness and potential complications of the procedure limit its clinical use. Radionuclide ventriculography (RVG) has been regarded as the best noninvasive method in identifying subclinical anthracycline cardiotoxicity in adult patients (Alexander et al, 1979;Schwartz et al, 1987;Ganz et al, 1996). Guidelines based on changes in systolic and diastolic left ventricular function have been given for monitoring patients receiving anthracycline therapy (Alexander et al, 1979;Schwartz et al, 1987;Ganz et al, 1996).…”
mentioning
confidence: 99%
“…This toxicity is characterized by progressive myocyte damage that can lead to dilated cardiomyopathy and refractory congestive heart failure. 2 The mechanisms that underlie the cardiotoxicity are only partially understood. Possible mechanisms include direct or indirect release of endogenous toxins (eg, histamine), 3 alterations in intracellular calcium homeostasis, 4 generation of free radicals that damage cellular membranes, 5,6 and intercalation of drug in the nuclear and mitochondrial genome, resulting in diminished RNA and protein synthesis.…”
mentioning
confidence: 99%
“…Quantitative radionuclide angiocardiography has been established as the preferred method of monitoring patients treated with anthracyclines [25][26][27] and can identify patients at a high risk of developing significant cardiac toxicity. In a retrospective study, Schwartz et al 26 found that in patients treated with doxorubicin, a decline of 10% or more in absolute LVEF to a value of 50% or less, as determined by ERNA, identified patients who subsequently developed clinical congestive heart failure if therapy with doxorubicin was continued.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%